The Role of Fanaticism and Self-Control as Factors Influencing K-Popers' Aggressive Behavior and Its Impact on Mental Health - Hanif Megantoro; Reni Silviah (Greenation Publisher & Yayasan Global Research National, 2026)
Literature Review of the role of fanaticism and self-control as factors influencing aggressive behavior of K-popers and its impact on mental health is a scientific article with the aim of analyzing whether fanaticism and self-control play a role in aggressive behavior and mental health. The research method used is a literature review with a descriptive qualitative approach, which aims to examine the results of previous studies on fanaticism and self-control as factors influencing aggressive behavior of K-popers and its impact on mental health. The results of this article are: 1) Fanaticism plays a role in aggressive behavior of K-popers, 2) Self-control plays a role in aggressive behavior of K-popers, 3) Fanaticism plays a role in the impact on mental health, 4) Self-control plays a role in the impact on mental health. Apart from these 2 exogenous variables that influence endogenous variables of aggressive behavior, there are many other factors including emotional regulation, anxiety, parenting style, frustration.